Time in blood pressure range for different blood pressure targets and risk of cardiovascular disease: an analysis of a 7-year follow-up registry. (25th November 2020) - Sideris, K; Kasiakogias, A; Konstantinidis, D; Papakonstantinou, P; Tatakis, F; Kouremeti, M; Tsioufis, P; Anastasiou, A; Leontsinis, I; Manta, E; Tousoulis, D; Tsioufis, C
Abstract: Objective: Recent guideline recommendations have revisited the optimal target blood pressure (BP) for hypertensive patients. The Time in BP Range (TBPR) is an alternative metric for evaluation of long-term achieved BP. We investigated the association of TBPR for different levels of BP control with cardiovascular outcome among treated hypertensives. Design and method: This is a retrospective analysis of 1202 treated hypertensive patients (age 59±11 years) without a history of cardiovascular disease followed for a mean period of 7±3 years. We calculated the TBPR [(No of Visits in BP range/ Total No of Visits) x 100%] for office systolic BP targets of 130–139mmHg, 120–129mmHg and <120mmHg and examined the associated cardiovascular risk. The outcome studied was the composite of stroke and coronary artery disease. Time spent in systolic BP≥140mmHg served as the reference. Results: In the entire population, mean TBPR for systolic BP 130–139mmHg, 120–129mmH, and <120mmHg were 26%, 19% and 11% respectively. A TBPR of ≥50% for systolic BP 130–139mmHg, 120–129mmHg and <120mmHg was observed in 332 (28%), 226 (19%) and 107 (9%) patients respectively. The composite endpoint occurred in 54 patients (4.5%). Patients with a TBPR for 120–140mmHg of ≥50% presented with a HR: 0.6 (95% CI: 0.34–1.06) for cardiovascular events. The TBPR of ≥50% for systolic BP 130–139mmHg, 120–129mmHg and <120mmHg was associated with HR of 0.48 (95% CI: 0.23–1.01, p=0.05), 0.64 (95% CI: 0.29–1.39, p=0.26) and 0.72 (95% CI: 0.26–2.05) respectively. This pattern was sustained but further attenuated after controlling for standard risk factors. In comparison, a mean BP across visits of 130–139mmHg, 120–129mmHg and <120mmHg was associated with a HR of 0.54 (5% CI: 0.28–1.03), 0.61 (95% CI: 0.29–1.26) and 0.80 (95% CI: 0.24–2.65). Conclusions: Among treated hypertensives, a time in BP of 130–140mmHg of more than 50% is associated with the greatest reduction in cardiovascular risk. The TBPR is a potentially useful measure of BP control for evaluation of risk reduction in hypertensive patients. Funding Acknowledgement: Type of funding source: None